Characterization of VAMP-2 in the Lung: Implication in Lung Surfactant Secretion - Wang, Pengcheng (2012)
Lung surfactant is crucial for reducing the surface tension of alveolar space, thus preventing the alveoli from collapse. Lung surfactant is synthesized in alveolar epithelial type II cells and stored in lamellar bodies before being released via the fusion of lamellar bodies with the apical plasma membrane. The soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNARE) play an essential role in membrane fusion. We have previously demonstrated the requirement of t-SNARE proteins, syntaxin 2 and SNAP-23, in regulated surfactant secretion. Here, we characterized the distribution of vesicle-associated membrane proteins (VAMPs) in rat lung and alveolar type II cells. VAMP-2, 3 and 8 were shown to be present in type II cells at both mRNA and protein levels. VAMP-2 and -8 were enriched in lamellar body fraction. Immunochemistry studies indicated that VAMP-2 was co-localized with the lamellar body marker protein, LB-180. Functionally, the cytoplasmic domain of VAMP-2, but not VAMP-8 inhibited surfactant secretion in type II cells. This study suggests that VAMP-2 may be the v-SNARE involved in regulated surfactant secretion.